An Analysis of the Causal Relationships in Sustainable Consumption Behaviour (SCB) of Thai Student Science Teachers - Pimdee, Paitoon (My University, 2021)
Having its originations in the 1987 UN Brundtland Report and the 1994 Oslo Symposium for sustainable consumption and production (SCP), education for sustainable development (ESD) has taken on global importance. As such, the study’s author sought to examine the causal relationships on sustainable consumption behaviour (SCB) of Thai student science teachers, as these are the leaders of tomorrow. The sample of 200 men and 200 women was obtained by use of multistage random sampling from ten state universities located across 5 Thai regions. The research tool was a 5-level response questionnaire consisting of 130 total items examining 18 observed variables, of which 97 items were positive in nature, while the remaining 33 items were negative in nature. The IOC was used to assess the questionnaire’s development process by the three teacher training experts. Subsequent item reliability testing of the pilot test group of 62 individuals used Cronbach’s Alpha (α) to judge reliability. Further data analysis made use of LISREL 9.1 software on the interrelationships of the latent variables psychological state (PS), environmental education (EE), psychological traits (PT), situation (SIT), as well as their effect on SCB. Results revealed that all the model’s causal variables had a positive effect on SCB, which can be explained by the combined influence of the factors (R2) being 92%. Furthermore, four factors were determined to influence SCB. Ranked in importance, these included SIT, EE, PS, and PT.
Keywords: education for sustainable development; ESD; SDGs; student situation; sustainable development goals; Thailand